(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2025)
Parkinson’s disease is a progressive neurodegenerative disorder marked by motor and non-motor symptoms due to dopaminergic neuron loss in the substantia nigra. Its complex etiology genetic, environmental, and age-related hinders development of disease-modifying therapies. To understand PD pathogenesis and evaluate potential therapeutics, various experimental models have been developed. Alterations in PD-associated genes have been used to develop animal and cell models. In-vitro models (Culture of Substantia Nigra and MTT+ Assay by Neuroblastoma SH-SY5y Cells (In-vitro approaches, including the use of SH-SY5Y cell lines and primary neuronal cultures, offer high-throughput platforms for mechanistic studies and drug screening) and In-vivo (Neurotoxin-induced, pharmacological, genetic models,). Neurotoxins such as MPTP, 6-OHDA, and rotenone are widely used to mimic dopaminergic neurodegeneration in animal models and in pharmacological model such as Haloperidol-Induced Model, Tremorine and Oxotremorine, Reserpine. Genetic models utilize mutations in PD-related genes (e.g., SNCA, PARK2, PINK1, LRRK2) to simulate familial PD. In these each model offers unique advantages and limitations, and a strategic combination of these methods enhances translational relevance in PD research.